STUDENT PARTICIPATION AND TOLERANCE IN EDUCATIONAL GAMES: A CASE STUDY - Nur Khosiah; Mohammad Syaifuddin; Khozin (Universitas Islam Negeri Mataram, 2025)
The learning process at the elementary school level is still dominated by conventional approaches that are repetitive and lack participation and tolerance of students. In this context, the integration of game-based learning media (games) as a strategic alternative that has the potential to increase participation and tolerance that is relevant to the progress of the times. This study aims to describe the use of educational games in Civic Education (PKn) learning as an effort to increase participation and tolerance of elementary school students. This study uses a qualitative approach with a case study method at SDI Miftahul Huda Tongas, Probolinggo. Data collection techniques were carried out through observation, in-depth interviews, and documentation of the Princip, teachers and fourth grade students involved in game-based PKn learning. These results indicate that the game-based learning approach not only makes the learning atmosphere more enjoyable, but also strengthens the formation of national character in accordance with the objectives of the PKn subject at the elementary school level. The increase in participation includes: students answering questions from 30% after the game increased to 80%, group discussions from 40% to 85%, student enthusiasm from 35% to 90%, Cooperation with friends from 40% to 80%, sportsmanship and tolerance with friends from 40% to 80%. While in increasing tolerance, respecting friends from 40% to 80%, respecting opinions from 40% to 80%, reducing conflict from 35% to 85%, openness to cooperation from 40% to 85%, not being selfish from 40% to 80%.